Plus ça change, plus c’est pareil : The case of "que" in Montreal French - Warren, Jane (Culture)

(untitled) (Canadian Anthropology Society / Société Canadienne d’Anthropologie (CASCA), formerly/anciennement Canadian Ethnology Society / Société Canadienne d’Ethnologie, 1994)
This paper studies the use or nonuse of the word « que » in Quebec French. Historical records show that in Old French and in 17th century French, the word « que » is optional in sentences such as « Je pense que »... Looking at the occurrences of « que » found in the Sankoff-Cedergren and Montreal 84 corpora of spoken French, the author shows that the occasional absence of « que » in Quebec French today is not the resuit of an ill-educated misuse of the language, but is rather an option which has developed within a systematic grammar distinctive to Quebec. For reasons linked to the linguistic norm, this is an option that many people choose not to exercise.